Migration system formation and decline: a theoretical inquiry into the self-perpetuating and self-undermining dynamics of migration processes - de Haas, H (International Migration Institute, 2009)
The migration literature has identified various mechanisms which explain why, once started, migration processes tend to gain their own momentum and become self-perpetuating, partly independent of their original causes, leading to the formation of migration systems. However, existing theories on the internal dynamics of migration processes are characterised by three fundamental weaknesses. First, while they focus on the migration-facilitating role of migrant networks, they tend to ignore the indirect feedback dynamics that operate through the impact of migration on the sending and receiving contexts, altering the structural conditions under which migration initially took place. Second, existing theories are unable to explain why most initial migration moves do not lead to network migration and the subsequent establishment of migration systems. It is unclear under what conditions initial moves by pioneer migrants do result in rapidly expanding network migration and the formation of migration systems, and under which conditions this does not happen. Third, the central argument of existing theories is largely circular because according to their circular assumptions migration goes on ad infinitum. They offer surprisingly few insights into migration-undermining feedback mechanisms that may counteract self-perpetuating dynamics and may contribute to the decline of established migration systems over time. By drawing on various strands of the migration literature and by applying insights from the critical social capital literature, this paper proposes a comprehensive conceptual framework on the internal dynamics of migration processes by elaborating a set of hypotheses on the various migration-facilitating and migration-undermining feedback mechanisms at play at the various trajectories and stages of migration system formation and decline.